Gambling engagement mechanisms in Twitch live streaming. Issue 3 (1st September 2020) - Abarbanel, Brett; Johnson, Mark R.
ABSTRACT: This paper examines the ongoing gamblification of engagement mechanisms on the live streaming website Twitch.tv ( Twitch ). Twitch is the market-leading platform for live broadcast of digital games and digital gambling, with two million content creators reaching around one hundred and fifty million viewers per month. Streamers use a variety of monetization techniques to encourage fan engagement while generating revenue: this includes incorporating chance-based elements and unpredictable rewards, part of the ongoing broader convergence of gambling and gaming products. The primary research objective for this study is to investigate the chance-based mechanics in these stream interaction and engagement services, how they work, and how these mechanics fit within elements of traditional legal definitions of gambling: consideration, chance, and prize. Understanding how game spectators engage with streamers helps establish a foundation for understanding how emerging forms of media engagement fit within a policy landscape that might not be designed for technology-driven gambling and gaming consumption. The themes that emerge here have important implications for streamers who monetize, stream extension developers who operate in spaces where certain game mechanics may fall into gambling or other consumer protection oversight, and regulatory authorities who maintain that oversight.